Design of High Gain Novel Dielectric Resonator Antenna Array for 24 GHz Short Range Radar Systems - Haddad, A.; Aoutoul, M.; Rais, K.; Essaaidi, M.; Faqir, M.; Bouya, M. (Advanced Electromagnetics, 2018)
in this work we present a 16x1 array’ elements of a high gain Novel shape designed Dielectric Resonator Antenna (NDRA), having a low dielectric constant value of 18, for wide band (WB) and narow band (NB) 24 GHz automotive Short Range Radar (SRR) applications. The proposed NDRA array is feed by an efficient microstrip network feeding mechanism and presents wide impedance bandwidth (426 MHz), high gain (20.9 dBi), high efficiency (96%) and directional radiation pattern at 24 GHz with narrow angular beam-width of 6.4°. Computed NDRA array results allow the proposed design to be practical for the next automotive radar generations. Parametric studies have been analyzed using the Finite Difference Time Domain (FDTD) method of the CST-MW time domain solver and results, of the optimal structure, have been validated by the Finite Element Method (FEM) used in HFSS electromagnetic (EM) simulator.